Critical care admission trends and outcomes in individuals with bronchiectasis in the UK - Navaratnam, Vidya; Muirhead, Colin R.; Hubbard, Richard B.; De Soyza, Anthony (Oxford University Press, 2015)
Background: There are limited data on admission trends and outcomes of individuals with bronchiectasis admitted to intensive care (ICU). Using national critical care data, we analysed admissions to ICU and estimated outcomes in terms of mortality in individuals with bronchiectasis and chronic obstructive pulmonary disease (COPD) admitted to ICU.